The Problem of (Inter)Theoretical Incompatibility in Science - Salas Llanas, Israel (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Throughout the history of science, major paradigm shifts have invariably been preceded by extended periods of irreconcilable dialogue between competing worldviews. The coexistence of mutually incompatible models —each vying to provide a unifying mathematical framework for physical reality— has long been a subject of profound philosophical scrutiny. This paper examines the problem of intertheoretical incompatibility in science and its enduring significance in contemporary philosophical discourse.